QUANTIFYING POLYCENTRIC PATTERNS: AN EMPIRICAL APPLICATION ON EMPLOYMENT DATA IM MOLDOVA, ROMANIA - Alexandra BLĂGEANU (European Journal of Geography)
Polycentrism has been in the academic limelight ever since it was promoted in European Spatial Development Perspective as an a-priori view valuable to adopt. The scientific literature is abundant in studies which approach this concept from both a normative and an analytical point of view. The latter offers different methods for analysing polycentric patterns of development of a region. This paper uses elements of spatial econometrics to identify such patterns in Moldova – the eastern side of Romania. Hence, different indexes of spatial autocorrelation will statistically describe the spatial pattern of employment in Moldova revealing its spatial structure (scattered or polycentric) and will then be incorporated in a hot spot analysis which will point out spatial cluster topologies. The final output can serve as a starting point for further detailed analysis and in assessing the implications of the identified spatial structures on decisional level (stakeholders and policy designers).